Bridging Knowledge Creation and Conservation Practice through Participatory Action Research on Private Lands. (8th February 2023) - Taylor, Matthew; Davison, Aidan; Harwood, Andrew
Ongoing failure to resolve how wildlife and people can co-exist on private land contributes to the global decline of wildlife populations. Experience in Tasmania, Australia suggests a disconnect between wildlife researchers, environmental agencies, and private landholders that prevents new scientific insights from translating into improved wildlife management practices. This case study based on a participatory action research model, describes a wildlife conservation initiative called WildTracker. WildTracker created hands-on collaborations among private landholders, university researchers, and the Tasmanian Land Conservancy (TLC). Landholders from 3 regions (total area 9977 km 2 ) participated in an iterative 2-year research process involving problem-framing workshops, data collection (mammals, birds, and habitat) using wildlife cameras and sound recorders, data analysis, and discussion of results. Participants contributed more than 2, 000 hours to the project, resulting in more than 500, 000 wildlife observations, with many landholders now implementing research findings, guided by locality-specific data on wildlife populations, feral animals, and habitat condition. WildTracker has evolved from a short-term participatory research project into an ongoing collaborative citizen science program that is documenting and contributing to on-the-ground and evolving wildlife conservation outcomes.